THE PLACE OF STRONTIUM RANELATE IN THE TREATMENT OF PATIENTS WITH OSTEOPOROSIS (RESULTS OF THE MARC PROGRAM) - O. A. Nikitinskaya; N. V. Toroptsova; E. L. Nasonov (Научно-практическая ревматология)
Strontium ranelate (SR) that has a proven efficacy in reducing the risk of fractures and in increasing bone mineral density is currently recommended as a second choice drug for the treatment of severe osteoporosis (OP) in postmenopausal women and elderly men. Subjects and methods. In 2014–2015, a survey within the framework of the MARC program (The Use of Antiosteoporotic Drugs in Real Clinical Practice) was conducted in 1799 OP patients aged 25 to 92 years, who had been treated for this disease for at least one year. Among the respondents, there were 1696 people aged 50 years and older (mean age, 64±7 years; disease duration, 2.7±2.4 years) (86% women and 14% men) who were the subjects of this survey. Adherence to performed antiosteoporotic therapy was evaluated within the last 12 months before the survey by the following parameters: which drug had been taken; the number of packages used, treatment gaps and compliance with the treatment regimen. Results and discussion. The survey of the patients included in the study showed that 19% of them had received SR at any time over the course of the disease, and 8% had taken the drug within the year preceding the survey. Thus, SR remains a popular drug in real clinical practice for the treatment of severe OP in patients with no history of coronary heart disease, uncontrolled hypertension, cerebrovascular diseases, peripheral artery disease, and a predisposition to thrombosis and thromboembolism.